'Strangely comforted': The rhetoric of sincerity in Kirsten Lepore's Hi Stranger. Issue 2 (1st September 2021) - Kriel-de Klerk, Johanet; Rossouw, Martin P.
This article examines the 2017 viral short film sensation, Kirsten Lepore's Hi Stranger, with special attention to the weird, even unsettling, potency that her stop-motion animation manages to wield. Why is it that this admittedly 'creepy' short ultimately leaves viewers and commenters 'strangely comforted'? A rhetorical solution to this question is proposed: Hi Stranger's creepy-yet-comforting appeal derives from the density with which it incorporates an array of rhetorical devices and affective registers ‐ particularly the 'rhetoric of sincerity' indicative of a more general 'metamodern' sensibility. The intensified sincere rhetoric at work in Hi Stranger moreover has a decidedly reflexive dimension, for this online crowd-puller draws on many devices and registers popular in amateur online videos too: its offers of low-stake, anonymous intimacy and no-strings gifting; its ASMR and 'cute' appeal; and its self-professed care and appreciation for the viewer.